Agile Marketing and its Role in Achieving Institutional Excellence: An Analytical Study of Dor Al Khaleej Mineral Water Manufacturing Company: Agile Marketing and its Role in Achieving Institutional Excellence: An Analytical Study of Dor Al Khaleej Mineral Water Manufacturing Company - Shritham, Muslim (The Gulf Economist, 2023)
This study tries to find out what Agile Marketing is? And what are its requirements? What is institutional excellence? and what are the dimensions? The extent to which the company in question has adopted the dimensions of Agile Marketing. In addition to determining the level of achievement of the mentioned company for institutional excellence. The study was applied in Dar Al Khaleej Mineral Water Manufacturing Company. This company has a noticeable share in Basra markets. It has received the human market’s attention for the distinguished products offered. The researcher chose a stratified random sample of (65) individuals to reach the following findings: Dar Al Khaleej Mineral Water Manufacturing Company adopts modern methods in the field of marketing, through the use of a group of specialists, who contributes in increasing the sales on one hand and achieving the company’s institutional excellence on the other. Dar Al Khaleej Company focuses on delivery on time, and thus it adopts a policy of partnership with suppliers on the one hand, and with customers on the other. The statistical results showed that there are a significant correlation between lean marketing and institutional excellence, and a significant effect relationship was found also between agile marketing and institutional excellence.